Generation of High‐Order All‐Aqueous Emulsion Drops by Osmosis‐Driven Phase Separation. Issue 39 (17th August 2018) - Chao, Youchuang; Mak, Sze Yi; Rahman, Shakurur; Zhu, Shipei; Shum, Ho Cheung
Abstract: Droplets containing ternary mixtures can spontaneously phase‐separate into high‐order structures upon a change in composition, which provides an alternative strategy to form multiphase droplets. However, existing strategies always involve nonaqueous solvents that limit the potential applications of the resulting multiple droplets, such as encapsulation of biomolecules. Here, a robust approach to achieve high‐order emulsion drops with an all‐aqueous nature from two aqueous phases by osmosis‐induced phase separation on a microfluidic platform is presented. This technique is enabled by the existence of an interface of the two aqueous phases and phase separation caused by an osmolality difference between the two phases. The complexity of emulsion drops induced by phase separation could be controlled by varying the initial concentration of solutes and is systematically illustrated in a state diagram. In particular, this technique is utilized to successfully achieve high‐order all‐aqueous droplets in a different aqueous two‐phase system. The proposed method is simple since it only requires two initial aqueous solutions for generating multilayered, organic‐solvent‐free all‐aqueous emulsion drops, and thus these multiphase emulsion drops can be further tailored to serve as highly biocompatible material templates. Abstract : High‐order emulsion drops with an all‐aqueous nature, which are driven by osmosis‐induced phase separation within nonequilibrium aqueous two‐phase systems, are achieved in a microfluidic platform. Based on the initial concentration of the two aqueous phases, the complexity and mass transfer process are well captured in a state diagram, providing guidance to fabricate all‐aqueous emulsions with high‐order structures.